Mesoscopic revelations: studying the shape of AOT reverse micelles - Gale, Christopher D., author; Levinger, Nancy E., advisor; Krummel, Amber, committee member; Prieto, Amy, committee member; Buchanan, Kristen, committee member (Colorado State University. Libraries, 2024)
Aerosol-OT (AOT) reverse micelles are a quintessential model system for studying nanoconfinement, creating consistent reverse micelles with a repeatable and very small size (~1-10 nm) using just 3 components. These reverse micelles have been used for studying the behavior of water and solutes in nanoconfinement, modeling the behavior of key solutes and proteins in a system more analogous to in vivo work, synthesizing nanoparticles, and even as a vehicle for suspending proteins in a low-viscosity solvent for high quality NMR experiments. Despite their usefulness, AOT reverse micelle's shape is poorly understood, but important to understanding behavior within a reverse micelle. Interfacial properties have been found to be key to many aspects of behavior within AOT reverse micelles and distance from the interface as well as the actual amount of interface present are highly dependent on shape. Therefore, the study of shape is key to a better understanding of AOT reverse micelles and behavior in nanonconfinement. In this work, I develop a series of metrics for shape--- coordinate-pair eccentricity (CPE), convexity, and the curvature distribution--- and apply them to several simulations of AOT reverse micelles. The simulations were designed to test the impact of the force field on the shape and behavior of the reverse micelles, including the first parameterization of AOT into the OPLS force field. The system was extensively checked to ensure equilibration was achieved and the system was not biased by the starting configuration. To aid in the shape analysis, I have developed a model and a formal proof to predict how the CPE changes for an arbitrary shape as it grows to model the shape behavior of general core-shell structures. Additionally, I measured the dipole moment of AOT, the rotational anisotropy decay of water, and several radial distribution functions to provide experimental verification where possible and further explore the behavior of the AOT reverse micelle system. Several key findings emerge from this work. Most notably, I find that AOT reverse micelles are significantly aspherical and non-convex over every force field tested, providing robust evidence that AOT reverse micelles are aspherical at any given moment in time. This provides strong evidence in support of the idea that experimental observations of spherical particles are the result of ensemble averaging. I also observe that the shape at the AOT/oil interface is comparatively more spherical with a "Goldilock's" value of convexity, neither too high nor too low, compared to the water/AOT interface. My model predicts that the CPE should fall with the addition of a shell, here provided by the AOT surfactant layer, suggesting this is largely the result of geometry. There is great variation between simulations and metrics in their dynamics, but in general, the shape appears to change on the order of 10 ns. This provides a useful method of deducing which values may or may not be impacted by shape, based on the time scale. For instance, it can reasonably be said that shape likely has no impact on water dynamics based on the roughly four orders of magnitude difference in the time scales of each process, which is supported by my own findings. Across all metrics studied, there are noticeable differences between simulations, but none of the differences are consistent. I believe this observation has important implications for both the behavior and simulation of AOT reverse micelles. First, this implies that the forces and interactions giving rise to different aspects of the reverse micelle are complex and largely independent, and that there is a disconnect between molecular-level measurements like radial distribution functions and and mesoscopic-level measurements like shape. Second, this implies that any simulation parameterized on one measure has no guarantee that it reproduces any other aspect of the reverse micelle accurately.
Keywords: AOT; coordinate pair eccentricity; shape; convexity; amorphous; reverse micelle